Groundwater policy: issues and alternatives in India - Moench, M. (International Irrigation Management Institute, 1996)
This paper reviews policy-related issues discussed in recent conferences that will affect groundwater development and management efforts in South Asia. Emphasis is given to policy issues surrounding emerging groundwater depletion and quality concerns, and issues concerning the equitable development of groundwater for poverty alleviation. The paper outlines the range of services that depend on groundwater resources and outlines the range of services that depend on groundwater resources to provide these services, and the complications stemming from the fragmented approach taken to water management throughout the region. A range of responses dealing with the management of the physical system is identified. In conclusion , the paper discusses institutional frameworks through which management responses could be implemented, in relation to both the range of approaches theoretically applicable and the existing institutional frameworks in place throughout South Asia